ChemInform Abstract: Magnesium‐Catalyzed Nitrile Hydroboration. Issue 18 (April 2016) - Weetman, Catherine; Anker, Mathew D.; Arrowsmith, Merle; Hill, Michael S.; Kociok‐Koehn, Gabriele; Liptrot, David J.; Mahon, Mary F.
Abstract: MGDA is the most efficient precatalyst in the reductive hydroboration of aliphatic and aromatic nitriles with pinacolborane (II).